Genocide and international justice - Frey, Rebecca Joyce (New York : Facts On File, 2009)
"Beginning with an introduction that defines the term genocide, Genocide and International Justice discusses the field of comparative genocide studies and outlines the stages of the Holocaust, which has become the template for evaluating and defining other genocides. The introduction is followed by detailed case studies examining ethnocide among Native Americans in the precolonial and early colonial period, the decimation of the Native American population during the colonial period, and the massacres and forced migrations of Native Americans in the 19th century. The book then looks beyond the United States to other acts of international genocide, including by the Mongols in Central Asia; the Armenian genocide; and the genocides in Cambodia, Rwanda, and Darfur. Efforts by the international community to prevent genocide and to prosecute those who commit such acts are also discussed." - BOOK JACKET.
Includes bibliographical references (p. 292-331) and index.
Keywords: Genocide -- History; Crimes against humanity -- History